2007
DOI: 10.1111/j.1365-3156.2007.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and associated factors in rural and urban populations of South Lebanon: a cross‐sectional community‐based study of self‐reported health in 2000

Abstract: Summaryobjective To assess self-reported morbidity and its determining factors in South Lebanon, with an emphasis on the influence of the habitat location (urban vs. rural) and gender.methods Cross-sectional survey in 2000 among 524 South Lebanon residents ‡14 years sampled from a random sample of households using a multi-level cluster sampling technique. Data on self-reported morbidity, lifestyle and socioeconomic status were collected through interviews, using a standardized questionnaire. To evaluate depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 18 publications
4
22
0
Order By: Relevance
“…It was also observed for Lebanese SF-36 social scores (Sabbah et al, 2003). A minor difference between urban and rural areas is also observed for the different scales scores of the SF-36 in Lebanon (Sabbah et al, 2003), and for the morbidity (Sabbah et al, 2007). These findings confirm the demographic and epidemiological transition phenomenon occurred in Lebanon (Sabbah et al, 2003).…”
Section: Cancer Childsupporting
confidence: 75%
See 2 more Smart Citations
“…It was also observed for Lebanese SF-36 social scores (Sabbah et al, 2003). A minor difference between urban and rural areas is also observed for the different scales scores of the SF-36 in Lebanon (Sabbah et al, 2003), and for the morbidity (Sabbah et al, 2007). These findings confirm the demographic and epidemiological transition phenomenon occurred in Lebanon (Sabbah et al, 2003).…”
Section: Cancer Childsupporting
confidence: 75%
“…This was also observed for Lebanese people aged 14 year and more using the SF-36 Health survey (Sabbah et al, 2003), which could be due to factors such as stress, morbidity of the parents (Duhamel, 2007), war status, lack of health coverage (Sabbah et al, 2007), lack of public green spaces (Costa, Vescina, & Barcellos Pinheiro, 2010), and comorbidities (Sabbah et al, 2003;Varni et al, 2003;Upton et al, 2005). Additionally, the physical functioning of children is low.…”
Section: Cancer Childmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is similar to that observed for the obesity, most morbidities [25], and f r different dimensions of o Notes & abbreviations: a n = 57: three (5.0%) patients were excluded from anthropometric analysis because lack of anthropometric measure (2 men, 1 woman). SD = Standard deviation; 50th percentile = median; Min = Minimum; Max = Maximum; n = Number of patients; Ci = Conicity index; WHR = Waist and hip ratio; BMI = Body mass idex; CCI = Charlson comorbidity index; URR = Urea reduction ratio.…”
Section: Predictors Of Comorbiditiessupporting
confidence: 74%
“…Studies reported higher obesity rates in urban than rural region [37][38][39][40][41][42]. Yadav & Krishnan [42] observed highest obesity prevalence among Indian urban residents of 5.5 % in men and 12.6 % in women.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%